2011
DOI: 10.1016/b978-0-444-53187-2.00012-7
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Social Networks and Economic Applications

Abstract: In this chapter I provide an overview of research on social networks and their role in shaping behavior and economic outcomes. I include discussion of empirical and theoretical analyses of the role of social networks in markets and exchange, learning and diffusion, and network games. I also include some background on social network characteristics and measurements, models of network formation, models for the statistical analysis of social networks, as well as community detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
147
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(156 citation statements)
references
References 238 publications
1
147
0
2
Order By: Relevance
“…Group activity is reflective of both social ties and shared interests, two variables that contribute to adoption, highlighting the complex interplay and potentially confounding nature of social influence and homophily [4], [16]. While we have demonstrated the utility of factoring in information about group membership to predicting adoption events, controlling for variables such as the number of friends in one's social circle who adopted, the present data analysis does not allow us to distinguish how much of the explanatory power of group membership is due to groups reflecting interests that would make an individual susceptible to adoption, and how much is due to activities within a group promoting adoption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Group activity is reflective of both social ties and shared interests, two variables that contribute to adoption, highlighting the complex interplay and potentially confounding nature of social influence and homophily [4], [16]. While we have demonstrated the utility of factoring in information about group membership to predicting adoption events, controlling for variables such as the number of friends in one's social circle who adopted, the present data analysis does not allow us to distinguish how much of the explanatory power of group membership is due to groups reflecting interests that would make an individual susceptible to adoption, and how much is due to activities within a group promoting adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars argue that homophily selection results in correlated attitudes and behaviors, making it difficult to determine a causal relationship between social influence and diffusion [4]. Some even argue that social influence and homophily are so highly intercorrelated that they can not be distinguished from one another [16].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Uzzi (1996) pointed out that the high level of uncertainty in hiring decisions can be reduced by the fine-grained information transfer in social-tie relations. Similarly, Jackson (2010) argued that social networks allow to mitigate substantial search frictions as they enable the communication of critical information to firms about the potential fit of workers. This mitigation of search frictions ends up in reduced search costs since decision makers are able to use trusted social contacts that are already in place, and need not to invest in constructing new ones (Granovetter, 2005).…”
Section: How Social Ties Influence Hiring Decisionsmentioning
confidence: 99%
“…However, the last two decades have seen a flurry of studies that have demonstrated that the effects of social networks on economic activity are abundant and pervasive, including roles in transmitting information about jobs, product adoption, technologies, and political opinion (Jackson (2008(Jackson ( , 2010). Several research papers have shown that information sharing with peers via social networks, word-of-mouth communication among people with whom we interact on a regular basis and shared education networks play an important role for investment decision making including stock market participation and portfolio choices.…”
Section: Introductionmentioning
confidence: 99%